More data, more credit? Information sharing and bank credit to households - Tamás Briglevics; Artashes Karapetyan; Steven Ongena; Ibolya Schindele (Magyar Nemzeti Bank, 2024)
We exploit a nation-wide introduction of mandatory disclosure of borrowers' total credit exposures and show that sharing such information increases credit access independent of borrowers' history. Differentiating between borrowers applying to competitor banks and those reapplying to their current banks, as well as between borrowers with and without default history, we find an overall increase in credit access measured by both loan application acceptance and credit amount. While credit access increases, default rates decrease, generating an increase in aggregate welfare.
Keywords: G21; G28; 330; information sharing; bank lending; household access to credit